2021
DOI: 10.1016/j.amsu.2021.102252
|View full text |Cite
|
Sign up to set email alerts
|

The role of early postoperative parathyroid hormone level after total thyroidectomy in prediction of hypocalcemia

Abstract: Background Estimation of parathyroid hormone (PTH) after thyroid surgery helps to predict the development of hypocalcemia and allows early intervention and management with oral calcium and/or vitamin D supplementation in the postoperative period. Patients and methods This retrospective study included 57 patients who underwent total or completion thyroidectomy within 4 years. Measurement of serum PTH level was done 3 h after surgery for its change and prediction of hypoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In some studies to predict hypocalcemia after bilateral total thyroidectomy, some authors have found success with a single parathormone measurement [11]. As in our study, studies examining the difference between preoperative and postoperative parathormone levels also report successful results [13,14].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In some studies to predict hypocalcemia after bilateral total thyroidectomy, some authors have found success with a single parathormone measurement [11]. As in our study, studies examining the difference between preoperative and postoperative parathormone levels also report successful results [13,14].…”
Section: Discussionsupporting
confidence: 73%
“…The median length of hospital stay was 4 (3-8.75) days. The mean preoperative calcium level was 11.04±0.86 (11) mg/dL, and after parathyroidectomy, the mean postoperative calcium level was 9.42±0.83 (9.5) mg/dL. The adjusted postoperative calcium mean was 9.34±0.78 (9.31) mg/dL.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The normal range of serum calcium level is 2.13-2.65 mmol/L. The blood calcium concentration is less than 2.00 mmol/L, hypocalcemia can be considered [12][13]. A blood calcium concentration of 1.90-2.00 mmol/L is considered mild hypocalcemia; blood calcium < 1.…”
Section: Observation Index and Postoperative Treatmentmentioning
confidence: 99%